2002
DOI: 10.1097/00003246-200204000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Hyponatremia in a pediatric stroke patient: Syndrome of inappropriate antidiuretic hormone secretion or cerebral salt wasting?*

Abstract: Cerebral salt wasting is associated with elevated plasma concentrations of ANP and BNP. Natriuretic peptides may play a role in the pathogenesis of this syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…The clinical findings are more consistent with CSW than SIADH as the cause of postoperative and postinjury fluid and electrolyte changes. Berger et al showed that the release of one or more natriuretic factors could also play a role in renal salt wasting seen in CSW, in addition to decreased neural input to the kidney (6). Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are important factors in clinically diagnosing CSW.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical findings are more consistent with CSW than SIADH as the cause of postoperative and postinjury fluid and electrolyte changes. Berger et al showed that the release of one or more natriuretic factors could also play a role in renal salt wasting seen in CSW, in addition to decreased neural input to the kidney (6). Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) are important factors in clinically diagnosing CSW.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological effects of these peptides include natriuresis and diuresis, aldosterone antagonism, relaxation of vascular smooth muscle cells, and direct antiproliferative effects on cardiac myocytes counteracting hypertrophy and destruction of sarcomere structure (1,2). Increased plasma concentrations of ANP and BNP are associated with hypertension, myocardial hypertrophy, arrhythmias, renal insufficiency, and cerebral salt wasting (3)(4)(5)(6)(7)(8). In myocardial infarction, concentrations of ANP, and especially BNP, were reported as a prognostic risk indicator independent from left ventricular ejection fraction (9 -14).…”
mentioning
confidence: 99%
“…CSWS is frequently associated with CNS hemorrhagic diseases, but only a few cases of CSWS in brain infarction have been reported [11-13]. The previous case reports of cerebral infarction had the characteristics of severe physical stress including systemic autoimmune disease, serious infection, and trauma (Table 2) [11,13].…”
Section: Discussionmentioning
confidence: 99%
“…The previous case reports of cerebral infarction had the characteristics of severe physical stress including systemic autoimmune disease, serious infection, and trauma (Table 2) [11,13]. These systemic complications might be more susceptible to developing CSWS than localized involvement in patients with cerebral infarction.…”
Section: Discussionmentioning
confidence: 99%